Preparation of Zn–Al layered double hydroxide intercalated with carboxymethyl-β-cyclodextrin by anion exchange method and its Ni2+ adsorption property. Issue 2 (3rd April 2021) - Kameda, Tomohito; Takaizumi, Mao; Kumagai, Shogo; Saito, Yuko; Yoshioka, Toshiaki
ABSTRACT: Recently, layered double hydroxides (LDHs) have been extensively researched for their anion exchange capabilities and exhibit a layered structure with a host layer of octahedrally coordinated metal cations and a guest layer (interlayer) of anions. In this study, we synthesized a CM-β-CDZn–Al LDH by anion exchange method to study the anionization of cyclodextrin (CD) to promote its incorporation into the LDH interlayers and its stability therein. Ni 2+ adsorption by the CMCDZn–Al LDH by the anion exchange method was compared with the results co-precipitation method. The X-ray diffraction spectra of NO3 Zn–Al LDH and CM-β-CDZn–Al LDH synthesized by the anion exchange method exhibit that the product peaks were attributable to Z n 6 A l 2 O H 16 C O 3 4 H 2 O and possessed an LDH structure. Furthermore, all CM-β-CDZn–Al LDHs exhibited the presence of some CM-β-CD. The CM-β-CDZn–Al LDH was hypothesized to be composed of two types of layers: a CM-β-CD layer in which two molecules of CM-β-CD 7 -, with cavity axes perpendicular to the LDH host layer, are vertically overlaid, and a NO3 -type Zn–Al LDH layer used as a precursor. CM-β-CDZn–Al LDH adsorbed Ni 2+ in an aqueous solution. To determine whether Ni 2+ adsorption by the CM-β-CDZn–Al LDH is driven chemically or physically, we fitted the data to the Freundlich and Langmuir adsorption models; the results showed that Ni 2+ adsorption by the CM-β-CDZn–Al LDH is consistent with the Langmuir equation and could be considered a chemical adsorption.